Genome Organization of Four Brazilian Xanthomonas albilineans Strains Does Not Correlate with Aggressiveness - Raquel P. Miranda; Paula C. G. Turrini; Dora T. Bonadio; Marcelo M. Zerillo; Arthur P. Berselli; Silvana Creste; Marie-Anne Van Sluys (Microbiology Spectrum, 2023)
ABSTRACT An integrative approach combining genomics, transcriptomics, and cell biology is presented to address leaf scald disease, a major problem for the sugarcane industry. To gain insight into the biology of the causal agent, the complete genome sequences of four Brazilian Xanthomonas albilineans strains with differing virulence capabilities are presented and compared to the GPEPC73 reference strain and FJ1. Based on the aggressiveness index, different strains were compared: Xa04 and Xa11 are highly aggressive, Xa26 is intermediate, and Xa21 is the least, while, based on genome structure, Xa04 shares most of its genomic features with Xa26, and Xa11 share most of its genomic features with Xa21. In addition to presenting more clustered regularly interspaced short palindromic repeats (CRISPR) clusters, four more novel prophage insertions are present than the previously sequenced GPEPC73 and FJ1 strains. Incorporating the aggressiveness index and in vitro cell biology into these genome features indicates that disease establishment is not a result of a single determinant factor, as in most other Xanthomonas species. The Brazilian strains lack the previously described plasmids but present more prophage regions. In pairs, the most virulent and the least virulent share unique prophages. In vitro transcriptomics shed light on the 54 most highly expressed genes among the 4 strains compared to ribosomal proteins (RPs), of these, 3 outer membrane proteins. Finally, comparative albicidin inhibition rings and in vitro growth curves of the four strains also do not correlate with pathogenicity. In conclusion, the results disclose that leaf scald disease is not associated with a single shared characteristic between the most or the least pathogenic strains. IMPORTANCE An integrative approach is presented which combines genomics, transcriptomics, and cell biology to address leaf scald disease. The results presented here disclose that the disease is not associated with a single shared characteristic between the most pathogenic strains or a unique genomic pattern. Sequence data from four Brazilian strains are presented that differ in pathogenicity index: Xa04 and Xa11 are highly virulent, Xa26 is intermediate, and Xa21 is the least pathogenic strain, while, based on genome structure, Xa04 shares with Xa26, and Xa11 shares with X21 most of the genome features. Other than presenting more CRISPR clusters and prophages than the previously sequenced strains, the integration of aggressiveness and cell biology points out that disease establishment is not a result of a single determinant factor as in other xanthomonads.